2021
DOI: 10.1007/s00405-021-06770-0
|View full text |Cite
|
Sign up to set email alerts
|

A survey of vocal health in church choir singers

Abstract: Purpose Choir singing is an important tradition of Christian worship across India. However, vocal health issues related to the church choir singers are less addressed in the literature. Hence, this study aimed to investigate the prevalence of vocal symptoms, identify the variables associated with increased risk of voice problems and knowledge of factors influencing vocal health in church choir singers. Method One hundred and forty-eight church choir singer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 22 publications
(39 reference statements)
2
10
0
Order By: Relevance
“…The prevalence of voice disorders in choir singers seems similar to that of teacher students and teachers (Ravall & Simberg, 2020). They frequently report vocal symptoms such as throat clearing, globus sensation or pain, a strained or tired voice, and hoarseness (Ravall & Simberg, 2020;Sharma et al, 2021). A recent study of Robotti et al (2021) showed higher self-reported voice and vocal tract impairments in amateur choir singers compared to control subjects.…”
Section: Introductionmentioning
confidence: 73%
See 4 more Smart Citations
“…The prevalence of voice disorders in choir singers seems similar to that of teacher students and teachers (Ravall & Simberg, 2020). They frequently report vocal symptoms such as throat clearing, globus sensation or pain, a strained or tired voice, and hoarseness (Ravall & Simberg, 2020;Sharma et al, 2021). A recent study of Robotti et al (2021) showed higher self-reported voice and vocal tract impairments in amateur choir singers compared to control subjects.…”
Section: Introductionmentioning
confidence: 73%
“…Due to high vocal demands, often combined with limited vocal knowledge and training, choristers are at risk for voice impairments (Braun-Janzen & Zeine, 2009;Reddy et al, 2014;Rosa & Behlau, 2017;Ravall & Simberg, 2020;Sharma et al, 2021;Robotti et al, 2021). This risk was visible in the PROMs with mean deviant scores on the SVHI-10 (14/40), VTDS (26/96) and VFI (21/96).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations